Keterbacaan Modul Sistematika Invertebrata: Hasil Uji dan Rekomendasi - Hasanah, Uswatun (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
The aim of this research is to determine the results of the readability test of the invertebrate systematics module that has been prepared and provide recommendations for improvement. This type of research is descriptive qualitative. The research instrument used was a student readability test sheet. The data analysis technique used is the percentage technique. Based on the results of the student readability test, an average of 3.22 was obtained, the module was declared very valid and suitable to be used as a reference source for Invertebrate Systematics teaching materials.